Swiss healthcare cost containment policies and their impact on anaesthetists’ density and satisfaction (Swiss Medical Weekly, 2011)
INTRODUCTION: To control healthcare costs, Federal and Cantonal states have introduced policies to limit expenses and the number of practising physicians. It is unclear to date whether these policies have had a real impact on anaesthetists in Switzerland. The aim of the current study was to assess the density, characteristics and satisfaction of anaesthetists in Latin Switzerland and to compare the results with data collected before the introduction of cost containment policies in 2002. METHOD: We performed a cross-sectional study between March and July 2009 and included all practicing anaesthetists in Latin Switzerland. A questionnaire consisting of 103 items analysing demographics, activity and job satisfaction was used. The results were analysed and compared to a previous survey conducted in 2002. RESULTS: Compared to 2002, there was an overall 12% increase in the number of practising anaesthetists who were older and more often females (42% versus 35% in 2002 (p = 0.06)). The number of non-Swiss anaesthetists significantly increased to 19% compared to 11% in 2002 (p